The Constitutionality of Regional Head Nomination Thresholds: A Perspective on Constitutional Court Decision No. 60/PUU-XXII/2024 - Muhammad Fikri; Muhammad Akbar Azhari; M. Bembo Jati Perdana (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The issue of the threshold requirement for regional head candidacy within Indonesia’s electoral system has long created disparities in political competition, particularly for small political parties that face difficulties in meeting the candidacy requirements. The relatively high threshold provisions stipulated in the Regional Election Law are considered to restrict the constitutional rights of political parties and potentially reduce the quality of local democracy. In this context, Constitutional Court Decision Number 60/PUU-XXII/2024 represents a significant turning point by lowering the threshold requirement for regional head candidacy. This study aims to analyze the constitutionality of the legal norms governing the threshold for regional head candidacy and the implications of the Constitutional Court’s decision on Indonesia’s democratic system. The research method used is normative legal research employing a statutory approach and a conceptual approach. The legal materials used include laws and regulations, court decisions, and relevant legal literature. The results of the analysis indicate that the reduction of the candidacy threshold by the Constitutional Court constitutes a constitutional measure to ensure the principles of equality and fairness in political rights, as guaranteed by the 1945 Constitution of the Republic of Indonesia. This decision expands access to political participation, particularly for small political parties and alternative candidates, and has the potential to improve the quality of local democracy through more open competition. The Constitutional Court’s decision not only corrects previously restrictive legal norms but also strengthens the protection of the constitutional rights of citizens and political parties while encouraging the realization of a more inclusive and representative democracy at the regional level.